Isoreticular expansion of polyMOFs achieves high surface area materials. Issue 77 (15th September 2017) - Schukraft, Giulia E. M.; Ayala, Sergio; Dick, Benjamin L.; Cohen, Seth M.
Abstract : Polymer–MOF hybrid materials (polyMOFs) are shown to adhere to the principle of isoreticular expansion, generating polyMOFs with large surface areas and enhanced stability. Abstract : The concept of isoreticular chemistry has become a core principle in metal–organic framework (MOF) materials. Isoreticular chemistry has shown that organic ligands of different sizes, but with a common geometry/symmetry can be used to generate MOFs of related topologies, but with expanded pore sizes and volumes. In this report, polymer–MOF hybrid materials (polyMOFs) with a UiO (UiO = University of Oslo) architecture are shown to adhere to the principle of isoreticular expansion, generating polyMOFs with large surface areas and enhanced stability.